ANALYSIS OF COMPUTER DESIGN PROGRAMS FOR SEWING ITEMS (Web of Technology: Multidimensional Research Journal, 2024)
This article discusses the advantages and disadvantages of computer-aided design programs for sewing products used in sewing enterprises.